Patient Involvement in the Lifecycle of Medicines According to Belgian Stakeholders: The Gap Between Theory and Practice - Janssens, Rosanne; van Overbeeke, Eline; Verswijvel, Lotte; Meeusen, Lissa; Coenegrachts, Carolien; Pauwels, Kim; Dooms, Marc; Stevens, Hilde; Simoens, Steven; Huys, Isabelle (Frontiers in Medicine, 2018)
BACKGROUND: Patient involvement is often acknowledged as an important aspect of the lifecycle of medicines. Although different typologies exist, patient involvement has been described as the involvement of patients in decision-making regarding medicines. In view of the diversity of stakeholders and types of decisions in which patients might be involved, an in-depth understanding of these stakeholders' views towards involving patients in the lifecycle of medicines is essential. METHODS: Interviews and surveys were used to gain insights into the perspectives and experiences of Belgian healthcare stakeholders. Interviews (n=22) were conducted with academics, hospital pharmacists and representatives from health insurance funds, the Belgian reimbursement agency, pharmaceutical industry and patient organizations. Interviews underwent a framework analysis. Surveys (n=108) were completed by hospital visitors and analyzed descriptively. RESULTS: Despite an increasing amount of efforts to involve patients, interviewees labelled the level of actively involving patients as rather low and scattered across the different phases of the lifecycle of medicines. The main opportunities for patient involvement highlighted by interviewees were for: i) informing early development decisions on which treatments to develop, ii) clinical trial endpoint selection and iii) clinical trial protocol design. However, remaining questions surrounding patient knowledge, and particularly how and which patients to involve represent important barriers towards implementing patient involvement in the lifecycle of medicines. Of survey participants, 77% indicated to be willing to participate in patient preference studies. Reasons for participating mentioned most frequently were "to improve development of treatments", because "it is important to explore and listen to patient preferences" and "to have a voice as patients". CONCLUSIONS: The barriers identified in this study hamper transitioning patient involvement from theory to practice. Bridging this gap requires addressing the identified barriers and unresolved questions surrounding the right methodology for involving patients, the 'right patients' to involve and means to increase patient knowledge. In order to do so, further research should focus on assessing the value of methods that allow to indirectly capture the patients' perspective both in the context of development as well as in the context of evaluation.